The First Photochromic Affinity Switch for the Human Cannabinoid Receptor 2 (Adv. Therap. 1/2018). Issue 1 (May 2018) - Dolles, Dominik; Strasser, Andrea; Wittmann, Hans‐Joachim; Marinelli, Oliviero; Nabissi, Massimo; Pertwee, Roger G.; Decker, Michael
Abstract : Photopharmacology The human cannabinoid receptor type 2 plays a central role in the immune system. In article no.1700032 Michael Decker and co‐workers report the development of photochromic affinity switches based on a drugable benzimidazole core through azologization and computational studies. Structureactivity relationships (SARs) lead to compounds with high selectivity over hCB1R that can be reversibly switched to a higher affinity cis ‐form, proved on the receptor level by radioligand binding studies and translating into an affinity change in a functional GTPγS assay. cAMP ELISA and the change in expression level of two genes regulated by CREB proves that the compounds act as partial agonists.